REIMAGINING CRIMINAL JUSTICE: OVERCOMING SYSTEMIC BARRIERS TO LEGAL PROTECTION FOR WOMEN THROUGH FEMINIST JURISPRUDENCE - Triantono, Triantono (Jurnal Hukum Progresif, 2025)
Violence against women remains a pervasive issue, affecting women physically, psychologically, socially, economically, and politically. Despite the existence of various laws, the barriers to accessing justice for women victims of violence remain substantial. These obstacles include revictimization, discriminatory legal procedures, and limited access to support services. Violence against women is rooted in systemic gender inequalities, where patriarchal cultural values often influence legal systems, perpetuating gender biases that undermine women’s ability to seek justice. Feminist jurisprudence challenges the traditional legal frameworks by questioning the so-called neutrality of the law. It emphasizes that the law, as it stands, often fails to protect women adequately due to the masculine perspectives embedded within it. By rejecting the objectivity of legal positivism, feminist jurisprudence advocates for a legal system that prioritizes the experiences of women, aiming for a more inclusive, victim-centered approach. This framework seeks to dismantle discriminatory legal structures and create an environment where women can safely access justice without fear of discrimination or retraumatization. In Indonesia, the enactment of the Sexual Violence Crime Law and the Supreme Court Regulation on adjudicating cases involving women have been significant steps toward addressing gender-based violence. These reforms reflect a shift toward victim-centered justice, focusing on protecting women and ensuring that their rights are upheld throughout the legal process. However, these laws can only be effective if they are supported by adequate resources, including victim assistance programs and trained law enforcement officials. Ultimately, the challenge lies in overcoming cultural and institutional barriers to justice. Strengthening access to justice for women requires not only legal reform but also a cultural shift toward gender equality. Feminist jurisprudence offers a holistic approach to this issue, calling for legal transformation, victim empowerment, and a supportive environment that enables women to fully participate in the justice process. By combining legal and societal changes, a more equitable legal system for women can be realized.